Kuguacin J, a triterpeniod from Momordica charantia leaf, modulates the progression of androgen-independent human prostate cancer cell line, PC3 - Pornsiri Pitchakarn (2018)
In this study, we focused on the in vitro effects of Kuguacin J (KuJ), a purified component of bitter melon (Momordica charantia) leaf extract (BMLE), on the androgen-independent human prostate cancer cell line PC3 and the in vivo effect of dietary BMLE on prostate carcinogenesis using a PC3-xenograph model. KuJ exerted a strong growth-inhibitory effect on PC3 cells. Growth inhibition was mainly through G1-arrest: KuJ markedly decreased the levels of cyclins (D1 and E), cyclin-dependent kinases (Cdk2 and Cdk4) and proliferating cell nuclear antigen. Interestingly, KuJ also dramatically decreased the levels of survivin expressed by PC3 cells. In addition, KuJ exerted anti-invasive effects on PC3 cells, significantly inhibiting migration and invasion: KuJ inhibited secretion of the active forms of MMP-2, MMP-9 and uPA by PC3 cells. In addition, KuJ treatment significantly decreased the expression of membrane type 1-MMP (MT1-MMP) by PC3 cells. In vivo, 1% and 5% BMLE in the diet resulted in 63% and 57% inhibition of PC3 xenograft growth without adverse effect on host body weight. Our results suggest that KuJ is a promising new candidate chemopreventive and chemotherapeutic agent for prostate cancer. © 2012 Elsevier Ltd.